IMPORTANCE OF APPLICATION OF SUSPENSIONS PREPARED ON THE BASIS OF MINERAL FERTILIZERS IN AGRICULTURE (Innovative Technologica: Methodical Research Journal, 2021)
The article finds that the effect of the suspension of cotton on the basis of different norms of KAS and urea fertilizers in the "Andijan-35" variety of cotton in the conditions of typical gray soils of Andijan region depends on the developmental stages of cotton. It has been proved that cotton has no effect on the yield of phosphorus and potassium fertilizers, which are insoluble in water in the suspensions used on farms, during the period of 2–3 leaves, mowing and flowering, only the optimal standards of suspension based on KAS and urea fertilizers should be applied.